CZY POLSKA POTRZEBUJE DZISIAJ PRAWDY O WOLNOŚCI I WYZWOLENIU GŁOSZONEJ PRZEZ KS. F. BLACHNICKIEGO? - Mikulski, Jan (Studia Pastoralne, 2023)
The truth about freedom and liberation is constantly threatened by a false notion of freedom and an erroneous assumption that freedom is to be found only where there is no external compulsion. According to Father Blachnicki, real freedom is born out of an internal overcoming of a hatred that makes one use violence and abuse as means to an end. Using the Gospel as the starting point he would promote the fight for liberation without violence, using the power of faith, that allows one to give testimony to the truth in every situation. He was of the opinion that actions aimed at the liberation of man should be seen as continuations of the salvific mission of Christ. In the face of alarming liberal attitudes that reject God’s rules in the name of incorrectly understood democracy it is worthwhile to bring to mind Father Blachnicki’s thesis that it is freedom that leads to liberation, not the other way round. For freedom is not a simple effect of liberation, and external liberation in itself does not guarantee the experiencing of internal freedom. Thus at the bottom of this pro-liberation pursuit there is an internal liberation which is liberation of man within man carried out in the process of formation of new man. Ultimately freedom is not an ability to do anything, but it is freedom towards Good which is the source of happiness. Man becomes free up to the point of his recognition of the truth and his will is driven by freedom. Theology of liberation presented by father Blachnicki is the application of theology of redemption to solving specific manifestations of enslavement among people of the contemporary era.